Distribution and antibiotic regulation of axe-txe toxin-antitoxin system in Enterococcus faecium clinical isolates - Mohd Irmal, Sri Indra Wahyuni (2018)
Toxin-antitoxin (TA) system consists of a pair of genes which are a stable toxin and an unstable antitoxin. The unstable antitoxin is known to be able to neutralize the toxin by interferes with the lethal action of toxin. These global regulators are ubiquitously present in some bacteria and involve in many metabolic functions. Due to the diversity of TA system, this research aimed to determine the distribution of axe-txe system among E. faecium. Recent finding has postulated the association of epsilon/zeta (ω-ε-ζ) TA system and cell wall synthesis (Mutschler, Gebhardt, Shoeman, & Meinhart, 2011). In the meantime, penicillin is capable to disturb cell wall synthesis of bacteria. Thus, synergy action that has been postulated at the target site by these two macromolecules (antibiotic and TA systems) was determined in this study. Meanwhile, chloramphenicol action as translational inhibitor has been associated with mazEF TA system and this was well studied in E. coli (Sat et al., 2001). Thus, give an insight for potential antimicrobial target. Hence, this current research was conducted to observe the association between axe-txe TA system in E. faecium and whether the expression of these two genes (axe-txe) would be induced or de-activated by penicillin and chloramphenicol in E. faecium. Twenty E. faecium isolates was collected and identified the axe-txe genes in both plasmid and DNA. Isolates with axe-txe TA system were chosen for determining the MIC of penicillin and chloramphenicol by visual turbidity and colorimetric assay followed by the MBC value. The colony forming unit of treated and untreated cultures within given time intervals were calculated and compared for both penicillin-resistant and chloramphenicol-sensitive strains. In both conditions, all RNAs were extracted and cDNAs were synthesized. The expression level of axe and txe genes were evaluated by real-time quantitative PCR (RT-qPCR) and the CT value obtained was calculated by using comparative CT method. All tests were done in triplicate. Twenty E. faecium clinical isolates possess the axe-txe TA system on both plasmid and chromosome. The MIC and MBC value were determined and will be used for next objective. The MIC and MBC values of chloramphenicol-sensitive E. faecium were 4 μg/ml and 32 μg/ml, respectively. Whereas, the E. faecium strain exhibited a resistance pattern towards penicillin with 256 μg/ml of MIC and 1024 μg/ml MBC. The expression level of axe and txe genes demonstrated the neutralizing effect to one another by forming a toxin-antitoxin complex. Under the stress conditions, the expression of axe gene within a given time interval was inhibited leaving the Txe toxin alone to react with intracellular target thus programmed cell death (PCD) was induced. The expression of Txe toxin in chloramphenicol-sensitive strain was gradually increased compared to penicillin-resistant strains. E. faecium showed a complex regulation of axe-txe TA system under stress conditions between penicillinresistant and chloramphenicol-sensitive strains. The axe-txe TA system is functional and transcribed in both chromosome and plasmid in E. faecium. The regulatory mechanism of this TA system could be explored further for potential antimicrobial targets in this pathogenic bacterium in future.